Method for rapidly evaluating performance of silicon-carbon negative electrode material of lithium ion battery
By testing the specific surface area changes of the silicon carbon negative electrode material before and after pressurization, calculating the ΔS value and comparing it with the reference value, the problem of complex and non-reproducible performance evaluation method for silicon carbon negative electrode material of lithium-ion batteries in the prior art is solved, and the effect of rapid evaluation of material performance is achieved.
Patent Information
- Application Number
- CN202411658521.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the performance evaluation method of lithium-ion batteries silicon carbon negative electrode material requires assembled buckle batteries or full batteries for cycle testing, with a long test cycle, cumbersome process, and poor reproducibility.
By testing the specific surface area change of the silicon carbon negative electrode material before and after pressurization, the ΔS value is calculated, and compared with the reference value ΔS0 to judge the material properties. The method includes measuring the specific surface area of the material to be tested, performing pressurization test, measuring the specific surface area of the sample after compression, and calculating the ΔS value.
This method can quickly evaluate the mechanical strength of silicon carbon negative electrode materials and the anti-expanding stress changes characteristics during long cycles, help with initial screening of materials, and achieve good correspondence with the performance of the whole battery.
Smart Images

Figure BDA0005142686490000021 
Figure BDA0005142686490000031 
Figure BDA0005142686490000051
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery testing, and in particular relates to a method for quickly evaluating the performance of silicon-carbon negative electrode materials of lithium-ion batteries. Background Art
[0002] With the rapid development of the new energy industry, lithium-ion batteries are gradually moving towards higher energy density. The existing graphite anode capacity can no longer meet the energy density requirements of future lithium-ion batteries. Silicon-based anodes have become the next generation of lithium-ion battery anode materials that can replace graphite due to their high theoretical gram capacity, rich content, and suitable lithium insertion potential.
[0003] Among the many silicon-based negative electrode materials, the emerging vapor-deposited silicon-carbon negative electrode has attracted much attention in the industry due to its excellent performance such as low expansion, good cycle stability and low cost. This material is made by introducing silane gas into a porous carbon substrate, and then pyrolyzing the silane to form nanoparticles that are deposited in the pores of the porous carbon substrate. The strength of the porous carbon substrate skeleton and the filling degree of silicon nanoparticles largely determine the mechanical strength of the material. Currently commercialized vapor-deposited silicon-carbon products are prone to fracturing under the high compaction density conditions in actual use. The exposure of the internal structure leads to an increase in side reactions during the cycle, which reduces the battery cycle performance and safety performance.
[0004] At present, the performance evaluation methods for silicon-carbon negative electrode materials for lithium-ion batteries mostly require the assembly of button cells or full batteries for cycle testing and evaluation. The test cycle is long, the process is cumbersome, and there are many process influencing factors, and the reproducibility is poor. In addition, the mechanical strength of the material can be judged by observing whether there are cracks on the surface of the silicon-carbon negative electrode particles through a scanning electron microscope after the electrode is rolled. However, this method has limited sampling area and high requirements for testing equipment, which is not conducive to practical promotion and application. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for quickly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries comprises the following steps: (1) measuring the specific surface area of the material to be tested, denoted as S A ; (2) The powder of the material to be tested is subjected to a pressure test according to the set compaction density; (3) The specific surface area of the sample after the test is recorded as S B ; (4) Calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0008] The specific surface area in steps (1) and (3) is measured by nitrogen adsorption method. Preferably, the test is performed using a Nova touch l x4 specific surface area tester;
[0009] In step (2), a pressure test is performed on a powder compaction density meter. The powder compaction density meter is a Yuanneng Technology Powder Compaction Density Meter PCD2000;
[0010] The mass of the material sample to be tested is 0.5-1.0g.
[0011] Step (2) Setting the compaction density to 0.8-1.8 g / cm 3 , preferably 1-1.2 g / cm 3 .
[0012] The pressure applied in step (2) is in the range of 5-500 MPa.
[0013] The compacted density is calculated according to formula 1,
[0014]
[0015] Wherein, ρ is the compaction density of the powder of the material to be tested, m is the mass of the powder to be tested, φ is the diameter of the carrier, and t is the thickness of the powder of the material to be tested.
[0016] The thickness of the powder to be tested is 0mm<t≤10mm.
[0017] The silicon-carbon negative electrode material is a chemical vapor deposited silicon-carbon negative electrode material.
[0018] In step (3), the material performance is determined by comparing ΔS with a reference value ΔS0, which is obtained based on the relationship between the performance of the silicon-carbon material and the full battery in the previous step.
[0019] When S A ≤2m 2 / g and S B ≤2m 2 / g, ΔS0=80%; when S A <2m 2 / g and S B >2m 2 / g, ΔS0=60%; when S A >2m 2 / g and S B >2m 2 / g, ΔS0 = 40%;
[0020] If ΔS<ΔS0, it means that the material can be used for further performance evaluation. If ΔS>ΔS0, it means that the material needs further improvement.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention tests the change in specific surface area of silicon-carbon negative electrode materials before and after pressurization, thereby determining the mechanical strength of silicon-carbon materials at a set compaction density and the material's anti-expansion stress change characteristics during a long cycle, helping with the initial screening of materials, and achieving a good correspondence with the full battery performance. The method is simple in sample processing and test operation, convenient and fast, and has good feasibility, and can be used to quickly evaluate the performance of silicon-carbon negative electrode materials for lithium-ion batteries. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the preferred embodiments.
[0024] Example 1
[0025] The silicon-carbon negative electrode material A obtained by chemical vapor deposition was selected to evaluate the material performance. The specific steps are as follows:
[0026] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0027] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it to a designed density of 1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0028]
[0029] Wherein, ρ is the compaction density of the powder of the material to be tested, m is the mass of the powder to be tested, φ is the diameter of the carrier, and t is the thickness of the powder of the material to be tested.
[0030] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0031] Example 2
[0032] Silicon-carbon negative electrode material A was selected to evaluate the material performance. The difference between this embodiment and embodiment 1 is that the designed compaction density is 1.1 g / cm 3 , the specific steps are as follows:
[0033] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0034] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0035] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0036] Example 3
[0037] Silicon-carbon negative electrode material A was selected to evaluate the material performance. The difference between this embodiment and embodiment 1 is that the designed compaction density is 1.2 g / cm 3 , the specific steps are as follows:
[0038] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0039] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.2g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0040] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0041] Example 4
[0042] Silicon-carbon negative electrode material A was selected to evaluate the material performance. The difference between this embodiment and embodiment 1 is that the sample weight is 1 g. The specific steps are as follows:
[0043] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0044] (2) Weigh 1g of sample and place it on the loading platform. Compact it to a designed density of 1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0045] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B, calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0046] Example 5
[0047] A silicon-carbon negative electrode material B is selected to evaluate the material performance. The difference between this embodiment and embodiment 1 is that the test sample is a silicon-carbon negative electrode B. The specific steps are as follows:
[0048] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0049] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it to a designed density of 1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0050] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0051] Example 6
[0052] Silicon-carbon negative electrode material B was selected to evaluate the material performance. The difference between this embodiment and comparative example 1 is that the designed compaction density is 1.1 g / cm3. The specific steps are as follows:
[0053] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0054] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0055] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0056] Example 7
[0057] The silicon-carbon negative electrode material B was selected to evaluate the material performance. The difference between this embodiment and comparative example 1 is that the designed compaction density is 1.2 g / cm 3 , the specific steps are as follows:
[0058] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0059] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.2g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0060] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0061] Example 8
[0062] A silicon-carbon negative electrode material C is selected to evaluate the material performance. The difference between this embodiment and embodiment 1 is that the test sample is a silicon-carbon negative electrode C. The specific steps are as follows:
[0063] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0064] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it to a designed density of 1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0065] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0066] Example 9
[0067] The silicon-carbon negative electrode material C was selected to evaluate the material performance. The difference between this embodiment and comparative example 4 is that the designed compaction density is 1.1 g / cm 3 , the specific steps are as follows:
[0068] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0069] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.1g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0070] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0071] Example 10
[0072] The silicon-carbon negative electrode material C was selected to evaluate the material performance. The difference between this embodiment and comparative example 4 is that the designed compaction density is 1.2 g / cm 3 , the specific steps are as follows:
[0073] (1) The specific surface area of the material to be tested is measured by nitrogen adsorption method, denoted as S A ;
[0074] (2) Weigh 0.5g of sample and place it on the loading platform. Compact it according to the designed density of 1.2g / cm 3 , calculate the thickness of the powder to be tested according to formula 1, perform a pressure test on the powder compaction density instrument, and record the equipment pressure value;
[0075] (3) The specific surface area of the sample after compression was tested by nitrogen adsorption method, denoted as S B , calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
[0076] The test results of the above embodiments and comparative examples are shown in Table 1:
[0077] Table 1
[0078]
[0079] It can be seen from the results in Table 1 that, by comparing Example 1 and Example 4, within the limited weight range, the sample weight has little effect on the test results, and the test results are only related to the material, indicating that the test method is reliable; by comparing Examples 1-3, under the conditions of the preferred design compaction density, the silicon-carbon negative electrode material A does not satisfy ΔS<ΔS0(S A <2m 2 / g and S B >2m 2 / g, ΔS0 = 60%), the silicon-carbon negative electrode material A needs to adjust the porous carbon substrate design to improve the mechanical strength of the carbon substrate to ensure that the manufactured battery meets the long cycle performance and safety requirements; By comparing Comparative Examples 1-3, the silicon-carbon negative electrode material B meets the requirements when S A >2m 2 / g and S B >2m 2 / g, ΔS<ΔS0=40%; By comparing Comparative Examples 4-6, the silicon-carbon negative electrode material C satisfies S A ≤2m 2 / g and S B ≤2m 2 / g, ΔS<ΔS0=80%; silicon-carbon negative electrode materials B and C can be used for further material evaluation.
[0080] Silicon-carbon negative electrode materials A, B and C were used as active materials to prepare batteries with the same other parameters. The results showed that the test method of the present application can achieve a good correspondence with the performance of the full battery.
[0081] In summary, the present invention tests the change in specific surface area of silicon-carbon negative electrode materials before and after pressurization, thereby determining the mechanical strength of silicon-carbon materials at a set compaction density and the material's anti-expansion stress change characteristics during a long cycle, helping with the initial screening of materials, and achieving a good correspondence with the full battery performance. The method is simple in sample processing and test operation, convenient and fast, and has good feasibility, and can be used to quickly evaluate the performance of silicon-carbon negative electrode materials for lithium-ion batteries.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries, characterized in that: The following steps are included: (1) measuring the specific surface area of the material to be tested, denoted as S A ; (2) The powder of the material to be tested is subjected to a pressure test according to the set compaction density; (3) The specific surface area of the sample after the test is recorded as S B ; (4) Calculate the change in specific surface area of the sample before and after pressurization ΔS = S B / S A -1, compare ΔS with the reference value ΔS0 to judge the material properties.
2. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: The specific surface area in steps (1) and (3) is measured by nitrogen adsorption method.
3. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: In step (2), a pressure test is performed on a powder compaction density instrument.
4. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: The mass of the material sample to be tested is 0.5-1.0g.
5. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: Step (2) Setting the compaction density to 0.8-1.8 g / cm 3 , preferably 1-1.2 g / cm 3 .
6. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: The pressure applied in step (2) is in the range of 5-500 MPa.
7. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: The compacted density is calculated according to formula 1, Wherein, ρ is the compaction density of the powder of the material to be tested, m is the mass of the powder to be tested, φ is the diameter of the carrier, and t is the thickness of the powder of the material to be tested.
8. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 7, characterized in that: The thickness of the powder to be tested is 0mm<t≤10mm.
9. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: The silicon-carbon negative electrode material is a chemical vapor deposited silicon-carbon negative electrode material.
10. The method for rapidly evaluating the performance of silicon-carbon negative electrode materials for lithium-ion batteries according to claim 1, characterized in that: In step (3), the material performance is determined by comparing ΔS with a reference value ΔS0, which is obtained based on the relationship between the performance of the silicon-carbon material and the full battery in the previous step. When S A ≤2m 2 / g and S B ≤2m 2 / g, ΔS0=80%; when S A <2m 2 / g and S B >2m 2 / g, ΔS0=60%; when S A >2m 2 / g and S B >2m 2 / g, ΔS0 = 40%; If ΔS<ΔS0, it means that the material can be used for further performance evaluation; if ΔS>ΔS0, it means that the material needs further improvement.
Citation Information
Patent Citations
Lithium ion battery positive electrode material precursor and preparation method and application thereof, lithium ion battery positive electrode material and preparation method and application thereof
CN115043440A
Negative pole piece, battery, battery pack and electric equipment
CN116404101A
Silicon-carbon negative electrode material and preparation method and application thereof
CN117117159A
Positive electrode material, preparation method thereof and lithium ion battery
CN117913269A
Silicon-carbon composite material, preparation method thereof, negative electrode and battery
CN118231603A
Cited By
Quantization method for cracking degree of lithium ion battery pole piece
CN121632758A